Dissipation-induced mobility and coherence in frustrated lattices - Owen, E. T.; Brown, O. T.; Hartmann, M. J. (Physical Review A, 2017)
In quantum lattice systems with geometric frustration, particles cannot move coherently due to destructive interference between tunneling processes. Here we show that purely local, Markovian dissipation can induce mobility and long-range first-order coherence in frustrated lattice systems that is entirely generated by incoherent processes. Interactions reduce the coherences and mobility but do not destroy them. These effects are observable in experimental implementations of driven-dissipative lattices with a flat band and nonuniform dissipation.
CRIS-Team Scopus Importer:2023-03-27